Congress tourism: Characteristics and application to sustainable tourism to facilitate collective action towards achieving the SDGs - Sandra Monroy-Rodríguez; Raquel Caro-Carretero (Cogent Business & Management, 2023)
The destination's tourism managers strategically invest in meeting infrastructure, aiming to host congresses and leverage the economic and social benefits of tourism to foster sustainable economic growth, inclusive employment and the realization of Sustainable Development Goal targets. Their efforts contribute to promoting a thriving economy, equitable job opportunities, and a sustainable future for all, as a Sustainable Development Goal (SDG). However, the mere fact of having basic facilities is not enough for the destination to be competitive in this segment. The aim of this paper is to identify those core factors that increase the competitiveness of the tourist destination in the congress segment. To identify the strengths and weaknesses of the congress tourism segment in the region of Extremadura, a study based on IPA (Importance-Performance Analysis) has been carried out on 21 determining factors selected from interviews with experts in the sector and after a thorough literature review. The diagram resulting from the IPA analysis has allowed us to obtain the strategic factors and theoretical and practical implications for both publics and private stakeholders. The result of this paper confirms the fundamental role of the public administration in improving the competitiveness of the congress tourism destination and key factors that directly affect the good development of congress tourism in a territory, such as the good relationship between public and private agents involved in the sector, tourism promotion and transport.
Keywords: 650; competitiveness; congress tourism; destination management; IPA analysis; priority factors